2005
DOI: 10.1203/01.pdr.0000182180.80645.0c
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Hypercapnia on Cerebral Autoregulation in Ventilated Very Low Birth Weight Infants

Abstract: Permissive hypercapnia, a strategy allowing high PaCO 2 , is widely used by neonatologists to minimize lung damage in ventilated very low birth weight (VLBW) infants. While hypercapnia increases cerebral blood flow (CBF), its effects on cerebral autoregulation of VLBW infants are unknown. Monitoring of mean CBF velocity (mCBFv), PaCO 2 , and mean arterial blood pressure (MABP) from 43 ventilated VLBW infants during the first week of life was performed during and after 117 tracheal suctioning procedures. Autore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
93
1
3

Year Published

2006
2006
2021
2021

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 169 publications
(101 citation statements)
references
References 32 publications
4
93
1
3
Order By: Relevance
“…17,18 Further, hypercapnia may abolish or impair cerebral autoregulation, causing the cerebral vasculature to be at risk for ischemia or hyperperfusion during fluctuations of blood pressure. [4][5][6] Consistent with our results, most studies examining the relationship between hypercapnia and IVH identified a positive univariate association. It was first demonstrated in 1978 that umbilical PaCO 2 was significantly greater in premature infants subsequently diagnosed with IVH compared to those without IVH.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…17,18 Further, hypercapnia may abolish or impair cerebral autoregulation, causing the cerebral vasculature to be at risk for ischemia or hyperperfusion during fluctuations of blood pressure. [4][5][6] Consistent with our results, most studies examining the relationship between hypercapnia and IVH identified a positive univariate association. It was first demonstrated in 1978 that umbilical PaCO 2 was significantly greater in premature infants subsequently diagnosed with IVH compared to those without IVH.…”
Section: Discussionsupporting
confidence: 91%
“…This is concerning given our recent observations that increasing PaCO 2 levels in VLBW infants are associated with progressively impaired cerebral autoregulation. 4 As impaired cerebral autoregulation in premature infants is associated with brain injury, 2,3 hypercapnia may influence the development of severe IVH by vasodilating cerebral resistance arterioles and increasing CBF, and possibly overwhelming the integrity of the germinal matrix vessels causing them to rupture. 17,18 Further, hypercapnia may abolish or impair cerebral autoregulation, causing the cerebral vasculature to be at risk for ischemia or hyperperfusion during fluctuations of blood pressure.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations